Effectiveness of application of carbon‐fibre polymer‐fabric resistive heating compared with forced‐air warming to prevent unintentional intraoperative hypothermia in patients undergoing elective abdominal operations: A systematic review and meta‐analysis of randomised controlled trials. Issue 23 (10th September 2020) - Zhang, Zhihui; Inman, Chris; Waters, David; Dee, Philip
Abstract: Background: Unintentional intraoperative hypothermia was regarded as a common intraoperative symptom with serious complications. The active warming strategies of forced‐air warming (FAW) and carbon‐fibre polymer‐fabric resistive heating were considered to be effective interventions for preventing hypothermia. However, the effectiveness of them was not reported consistently. Aim: To evaluate the effectiveness of carbon‐fibre polymer‐fabric resistive heating compared with FAW in preventing hypothermia in patients undergoing elective surgeries. Design: Systematic review and meta‐analysis. Methods: A rigorous systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis reporting checklist. Searching strategy was undertaken on the electronic databases of Cumulative Index to Nursing and Allied Health Literature, MEDLINE, PubMed, EMBASE and Medical Literature Retrieval Service. The assessment of study quality was performed through risk of bias of Cochrane handbook of systematic review of interventions. Data synthesis was conducted through meta‐analysis with sensitive analysis. The quality of evidence was graded using Grading of Recommendations Assessment, Development and Evaluation approach. Results: A total of five randomised controlled trials with 282 patients undergoing elective surgeries were included in the quantitative synthesis. Four studies concluded that FAW was as effective as carbon‐fibre polymer‐fabric resistive heating in preventing hypothermia. However, one study yielded a different conclusion that the efficacy of FAW was superior to carbon‐fibre polymer‐fabric resistive heating with small incidence of hypothermia. Meta‐analysis found that FAW was more effective than carbon‐fibre polymer‐fabric resistive heating in preventing hypothermia. Conclusions: In the elective abdominal surgery, carbon‐fibre polymer‐fabric resistive heating was less effective than FAW on the prevention of hypothermia. However, hypothermia still occurred in the FAW group. It was more objective to assess the efficacy of warming technology combining the incidence of hypothermia and the core body temperature together, which was suggested for further research.